Dangerous Materials: Control, Risk Prevention and Crisis Management From New Global Threats to New Global Responses: A Picture of Transition - Brugnoli, Alberto. (NATO Science for Peace and Security Series C: Environmental Security,, 2010)
We are living in a period of major structural and political transitions. The Post-Cold-War world has overcome the barriers, unifying Europe, sorting out Balkan situation, enlarging NATO and the EU; but, at the same time, it has shifted from a simple scenario to a more complex and unpredictable globalized context. In fact, many people wonder whether the world was more secure in the past than it is today or whether this is merely a matter of psychological perceptions. This publication is willing to answer to this question, by connecting the concepts of security and safety, focusing particularly on the transportation of dangerous materials, how to avoid the risks they pose, and how to deal with any problems that do arise.